Retail Business Readiness to Adapt to The Future and Scale - Manickum, Blain (University of the Witwatersrand, Johannesburg, 2023)
The retail industry has been mainly impacted by post covid-19 external changes such as an increase in e-commerce buying patterns, increased cost of debt, and reduction in earnings of consumers leaving retail businesses faced with difficult decisions to try to adapt to the changing markets or face closure. The purpose of the business venture proposal is to unpack specific problems Manix Hardware faces. These problems through research and literature reviews have been identified as the inability to grow past a growth ceiling, cashflow, the impact covid 19 had on consumers buying patterns, industry e-commerce trends, and lack of marketing skills. In order to detail these problems, a comprehensive literature review was conducted on management skills focusing on small business owners, marketing skills required, impact and adoption of technology, and gaining a greater understanding of the impact of covid 19 on the retail industry. Management theories and tools used as a framework of the business venture included PESTEL, customer analysis, porters model, resource-based view, and the business canvas model. These management theories allowed Manix Hardware to determine the extent of the problems and opportunities in detail. The research component of the business venture consisted of detailed entrepreneurial surveys that went out to business owners as well as customer surveys to further understand the needs of the consumer and how the business can improve and leverage on growth opportunities. Based on the research conducted key findings derived that there needs to be greater importance on innovative marketing efforts, improved business skills, financial financing models needs to be looked at, implementation of an e-commerce platform, and ways to remain sustainable post covid-19. v A comprehensive business, financial, operational, and implementation plan was then derived on how the identified problems and opportunities would then be executed using the specific management theories. Manix Hardware would improve on its online presence by creating an e-commerce platform for customers to purchase products online allowing them access to greater markets other than the two physical store locations, increasing their operating capital equipment allowing them to lower operating costs whilst improving efficiency and service delivery. Continuous training and development programs will be implemented upskilling their workforce and management team
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Retail Business; Future adaption; UCTD; SDG-8: Decent work and economic growth